Peran Etika Bisnis terhadap Keputusan Pembelian Ulang di Marketplace Shopee - Ismaul Janah; Winata Indriyani; Marissa Amelinda Penika; Budi Setyawan; Catur Wahyudi (CV. ITTC INDONESIA, 2026)
The development of marketplaces like Shopee has significantly changed people's shopping behavior. However, the rise of unethical business practices, such as misleading promotions, late delivery, and poor customer service, poses a challenge in maintaining consumer loyalty. This study aims to analyze the role of business ethics in repeat purchase decisions on the Shopee marketplace. The research method used a literature review, analyzing various journals, books, and related scientific articles. The results show that business ethics, consisting of honest information, price transparency, transaction security, service fairness, and seller responsibility, have a positive influence on repeat purchase decisions. Consumers are more likely to repeat purchases when they feel treated fairly, safely, and transparently by the seller and the platform. The implications of this research are important for businesses and marketplace managers to improve ethical business practices to build long-term loyalty.